2020
DOI: 10.1080/23311983.2020.1756146
|View full text |Cite
|
Sign up to set email alerts
|

The thematic structure in research article abstracts: Variations across disciplines

Abstract: This study has investigated the thematic structure of RA abstracts published in business administration, applied linguistics, accounting, physics, chemistry, and computer science disciplines from the perspectives of topical, textual, and interpersonal themes. The results showed that the unmarked topical themes were the most prevalent types in the RA abstracts, while the interpersonal themes were the least frequent. Concerning the textual themes, the results revealed some disciplinary variations. For example, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 19 publications
4
4
0
Order By: Relevance
“…This finding converges with several studies of Theme in RA abstracts (e.g. Alotaibi, 2020;Ebrahimi, 2016;Ghadessy, 1999). The low percentage of the interpersonal Theme type is in line with what would be expected in objective, non-evaluative scientific RA discourse (Gray & Biber, 2012;Hyland, 2005).…”
Section: Interpersonal Themesupporting
confidence: 92%
See 4 more Smart Citations
“…This finding converges with several studies of Theme in RA abstracts (e.g. Alotaibi, 2020;Ebrahimi, 2016;Ghadessy, 1999). The low percentage of the interpersonal Theme type is in line with what would be expected in objective, non-evaluative scientific RA discourse (Gray & Biber, 2012;Hyland, 2005).…”
Section: Interpersonal Themesupporting
confidence: 92%
“…This indicates the authors' awareness that maintaining the same entity (or topic) as the Theme of more than one clause develops a topic-focused text. This finding is in line with many studies (Alotaibi, 2020;Ebrahimi, 2016;Ebrahimi & Khedri, 2011;Ghadessy, 1999;Leong, 2016). For example, Leong (2016) investigated 200 RA abstracts from science and humanities disciplines and found that topical Themes were used more in scientific abstracts.…”
Section: Topical Themesupporting
confidence: 83%
See 3 more Smart Citations